1999
DOI: 10.1111/j.1151-2916.1999.tb02155.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Behavior of Manganese‐Doped Zinc Silicate Phosphors

Abstract: The purpose of the present study is to develop an understanding of the photoluminescence properties of Mn 2+ -doped zinc silicate (Zn 2 SiO 4 :Mn) phosphors, which have served as a gree-emitting phosphor in many industrial applications. Thus, several experimental techniques, such as time-resolved emission spectra, decay curves, and timeresolved photoluminescence excitation spectra, have been conducted on Zn 2 SiO 4 :Mn phosphors. The characterization has been performed in terms of dopant concentration. The dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 17 publications
2
37
1
1
Order By: Relevance
“…On calcining at 800-1000 • C, all of the powders were white, indicating that the manganese ions were in the divalent state [2,18]. XRD examination revealed that single-phase ␣-Zn 2 SiO 4 was formed by the present sol-gel approach with proper doping concentrations, suggesting that the Mn 2+ ions were well dispersed as substitutes for Zn 2+ in the zinc silicate host lattice after heating.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On calcining at 800-1000 • C, all of the powders were white, indicating that the manganese ions were in the divalent state [2,18]. XRD examination revealed that single-phase ␣-Zn 2 SiO 4 was formed by the present sol-gel approach with proper doping concentrations, suggesting that the Mn 2+ ions were well dispersed as substitutes for Zn 2+ in the zinc silicate host lattice after heating.…”
Section: Resultsmentioning
confidence: 99%
“…6. This peak is associated with the emission of Mn 2+ in the willemite lattice [2,4,18]. Following excitation by ultraviolet (UV) or visible light, the excited electrons relax to their lowest excited state ( 4 T 1 ) and then transition from 4 T 1 to the ground state ( 6 A 1 ) of Mn 2+ , emitting green light.…”
Section: Resultsmentioning
confidence: 99%
“…However, Mn 2+ ions can be directly excited in the wavelength range between 357 and 500 nm. 10,49 In particular, the 442 nm line (z2.81 eV) is resonant with the 4 T 2 ( 4 G) energy level. 50 From this level, the excited electrons can relax to the 4 T 1 ( 4 G) state through non-radiative processes and then radiatively decay to the ground state.…”
mentioning
confidence: 99%
“…10, 49 The luminescence in the green range originates from the transition of the 3d 5 electrons in the Mn 2+ ions -from the transition between the lowest excited state and the ground state: 4 T 1 ( 4 G) / 6 A 1 ( 6 S) of tetrahedrally coordinated Mn. 50 In this case, the zinc silicate host lattice absorbs energy and transfers charge efficiently to Mn ions.…”
mentioning
confidence: 99%
“…When doped with transition metal ions of cobalt this material is used as blue pigments in ceramic industry [1] while doping with manganese ions provides long persistent green phosphor with main applications in lamps and CRTs [2][3][4]. However, the utility of this phosphor as green component for plasma display panels is limited due to long decay time of Mn 2+ emission [5][6][7]. In our previous work we investigated, in more details, optical properties of Zn 2 SiO 4 powders doped with transition metal ions of Ni, Co and Mn [8].…”
Section: Introductionmentioning
confidence: 99%